HUBUNGAN ANTARA PERCEIVED ORGANIZATIONAL SUPPORT DENGAN EMPLOYEE ENGAGEMENT PADA KARYAWAN - Anwar, Rozan; Yuniasanti, Reny (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2024)
Objective: This study aims to determine the relationship between perceivedorganizational support and employee engagement at employees. Method: In thisstudy, the sample selection used purposive sampling with the criteria, hasworked for at least 3 months, so that 150 samples were obtained in this study.Result: From the data description, it is found that the results of the responses toemployee engagement show that as many as 77 or 51.3 employees have highengagement, 70 or 46.7%, and 3 or 2% have low engagement. While theperceived organizational support obtained by 24 employees or 16% have highperceived organizational support, 144 employees or 76% have moderateperceived organizational support and 12 people or 8% have low perceivedorganizational support. The results of the product moment correlation analysisshow that the correlation value (rxy) = 0.251 and p is 0.002 or less than 0.05.This shows that there is a positive relationship between perceivedorganizational support and employee engagement. Conclusion: This means thatincreasing positive perceptions about the extent to which the organizationvalues employee contributions and concerns for their welfare, the higher theirengagement. Conversely, increasing the negative perception of the extent towhich the organization values employee contributions and cares about theirwelfare, the lower the engagement applied.